A simple skew angle detection and suppression method for bit-patterned magnetic recording - Santi Koonkarnkhai; Chanon Warisarn; Piya Kovintavewat (AIP Advances, 2021)
An achievement of an areal density (AD) up to 4 Tb/in2 in hard disk drives (HDDs) is expected under a bit-patterned magnetic recording (BPMR) system. One of major problems in HDDs is a skew angle (SA), which depends on a read/write head position on a disk platter. Practically, if precaution is not taken, the SA can easily deteriorate the overall system performance. To maintain an acceptable system performance; therefore, we present a simple SA detection and suppression method for BPMR systems. Here, one readback sequence is used to compute a specific target coefficient before employing it to estimate the SA amount. To mitigate the SA effect, a couple of suitable two-dimensional (2D) target and its compatible one-dimensional equalizer associated with the estimated SA is utilized in the data detection process. We also propose the flipped-cross-track symmetric 2D target to reduce the complexity of the detector. Simulation results reveal that the utilization of our proposed SA method can improve the bit-error rate performance when compares with the conventional system that does not use the SA detection and suppression method, particularly when SA or AD is high.
Keywords: Magnetic properties of thin films; Block Copolymer Self-Assembly; Advancements in Photolithography Techniques